GAS PERMEABILITY OF GEOSYNTHETIC CLAY LINERS - Helena Vučenović; Dubravko Domitrović; Biljana Kovačević-Zelić (Rudarsko-geološko-naftni Zbornik, 2017)
Geosynthetic clay liners (GCL) are manufactured hydraulic barriers consisting of mineral and geosynthetic components. They belong to a group of geosynthetic products whose primary purpose is to seal and they have been used in many geotechnical and hydrotechnical applications, landfi lls and liquid waste lagoons for quite a while. They are used in landfill final cover systems to prevent the infi ltration of precipitation into the landfi ll body and the penetration of gases and liquids from the landfill into the atmosphere and environment. Laboratory and fi eld research and observations on regulated landfi lls have proven the eff ectiveness of GCL as a barrier for the infi ltration of precipitation into the landfi ll body as well as the drainage of fl uid beneath the landfill. Due to the presence of high concentrations of gases in the landfill body, there is a growing interest in determining the efficiency of GCL as a gas barrier. It was not until the last twenty years that the importance of this topic was recognized. In this article, current GCL gas permeability studies, the testing methods and test results of gas permeability in laboratory conditions are described.